(untitled) - Krause, E. (New York, 2005)
Despite dramatic advances in numerical and experimental methods of fluid mechanics, the fundamentals are still the starting point for solving flow problems. This textbook introduces the major branches of fluid mechanics of incompressible and compressible media, the basic laws governing their flow, and gasdynamics.
Keywords: Fluid mechanics; Problems, exercises, etc